Nickel-based methanation catalyst taking mesoporous molecular sieve SBA-16 as carrier and application of nickel-based methanation catalyst in carbon dioxide hydrogenation
By using mesoporous molecular sieve SBA-16 as a support, a nickel-based catalyst with high activity and long-term stability was prepared, which solved the problem of poor stability of existing catalysts at high temperatures, and achieved high efficiency and economicality of CO2 methanation reaction .
Patent Information
- Application Number
- CN202411490856.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-07
AI Technical Summary
The existing nickel-based catalysts are prone to sintering at high temperatures, have poor stability, and have a high temperature of CO2 methanation, resulting in catalyst deactivation and side reactions, making it difficult to achieve economical and efficient.
The mesoporous molecular sieve SBA-16 is used as a support to prepare a nickel-based catalyst through a specific method, including the steps of combining nickel salt with SBA-16 support, ultrasonic dispersion and vacuum drying, etc., to form a catalyst with high activity and long-term stability.
In the CO2 methanation reaction, the catalyst exhibits high activity and methane selectivity, the optimal reaction temperature range is 300-350°C, the CO2 conversion rate is 100.0%, the CH4 selectivity is at least 99%, and the catalyst has a long life.
Smart Images

Figure CN119386919A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a nickel-based methanation catalyst with a mesoporous molecular sieve SBA-16 as a carrier and an application thereof, and in particular to a nickel-based methanation catalyst prepared by a specific method and with a mesoporous molecular sieve SBA-16 as a carrier and an application thereof, belonging to the technical field of carbon dioxide methanation catalysts. Background Art
[0002] In recent years, with the continuous growth of the global population and economic scale, the environmental problems caused by CO2 emissions have become increasingly prominent. Although renewable energy has been used to reduce carbon dioxide emissions in recent years, the dependence on fossil fuels cannot be alleviated in the short term. In order to reduce the concentration of CO2 in the atmosphere, catalytic conversion of CO2 to produce energy chemicals has become an important research hotspot. This method can not only reduce the concentration of carbon dioxide in the atmosphere, but also improve energy infrastructure. Compared with other CO2 conversion reactions such as methanol, dimethyl ether, and formic acid, CO2 methanation has the advantages of high activity, low cost, and high energy efficiency. Due to its high flammability, methane is usually used as a fuel for daily life, and methane can also be used as a chemical raw material and is widely used in the manufacture of carbon monoxide, acetylene, and formaldehyde. Therefore, the use of CO2 to produce methane is of great significance to energy security, energy conservation, and emission reduction.
[0003] At present, most carbon dioxide methanation catalysts are supported catalysts. Among them, nickel-based catalysts have been widely studied in industry due to their low cost and high performance. However, nickel-based catalysts have the problems of easy sintering and poor stability at high temperatures. The development of highly active and highly stable CO2 hydrogenation to methane catalysts is the current research focus. Invention patent CN104971728 B discloses a core-shell CeO2-coated Ni methanation catalyst and its preparation method and application. Its special structure can effectively inhibit the sintering and agglomeration of active Ni components. However, its preparation process is complicated, and the optimal use temperature of the catalyst is above 340°C. The higher reaction temperature is easy to cause the catalyst to deactivate and the occurrence of side reactions. Patent CN202310870045.3 also discloses a reverse Ni / CeO2 catalyst and its preparation method and application. At 300°C, the CO2 conversion rate is 90% and the CH4 selectivity is 100%, but the preparation process is complicated and difficult to apply industrially, and the nickel content of 85wt% is very easy to cause the catalyst to sinter and deactivate at high temperature. In summary, in order to achieve the economy of the process, it is necessary to lower the CO2 methanation reaction temperature while ensuring high CO2 conversion rate, high CH4 selectivity and high stability.
[0004] The carrier usually affects the catalytic performance of the catalyst by affecting the interaction between the metal and the carrier and the dispersion of the active components. The highly ordered mesoporous SiO2 material is often used as a carrier for nickel-based catalysts because of its high specific surface area, porosity and unique ordered structure. In recent years, two-dimensional mesoporous molecular sieves such as MCM-41 and SBA-15 have been used as carriers for CO2 hydrogenation and methanation catalysts, but the research of D.Liu et al. (DOI:10.1016 / j.cattod.2009.08.014) shows that two-dimensional mesoporous materials still cannot fully suppress the poor stability of nickel-based catalysts at high temperatures, which limits their effectiveness in practical applications. The mesoporous molecular sieve SBA-16 has a unique ordered three-dimensional structure, high specific surface area and thermal stability. Its unique cage structure can prevent the thermal migration and sintering of active components at high temperatures, making it an extremely ideal carrier for catalytic reactions. The skeleton structure of SBA-16 is mainly composed of amorphous SiO2, and its surface contains a large number of silanol groups. Therefore, it cannot be directly used as a catalyst in catalytic reactions under normal conditions. Nickel metal can be introduced into the pores through wet impregnation to give it a certain catalytic activity. The preparation method is simple. Studies have shown (DOI:10.1021 / cs400159w) that nickel-based catalysts supported by SBA-16 have been used in CO2 catalytic utilization reactions, such as methane dry reforming. However, the application of SBA-16 in CO2 hydrogenation and methanation has received little attention, and this field needs further in-depth research and development. Summary of the invention
[0005] The purpose of the present invention is to provide a nickel-based catalyst prepared by a specific method using a mesoporous molecular sieve SBA-16 material as a carrier and its application in the hydrogenation of carbon dioxide to methane. The catalyst prepared by the method of the present invention exhibits high activity and long-term stability in the CO2 methanation reaction.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] A nickel-based catalyst with mesoporous molecular sieve SBA-16 as a carrier, characterized in that the catalyst is prepared by the following method, comprising the following steps:
[0008] 1) Preparation of mesoporous molecular sieve carrier SBA-16: dissolving triblock surfactant F127 in deionized water, adding hydrochloric acid solution and then adding tetraethyl orthosilicate and stirring, the molar ratio of each component is F126: hydrochloric acid: deionized water: tetraethyl orthosilicate = (0.001-0.01): (2-12): (2.5-7.5): (70-300): 1; after crystallization, filtration, drying, calcination and grinding, a mesoporous molecular sieve carrier SBA-16 white powder is obtained;
[0009] 2) dissolving the nickel salt in a solvent and adding an additive, preparing a precursor solution of a metal active component in a mass ratio of the additive to the nickel salt of (0-1.2):1, then adding the mesoporous molecular sieve carrier SBA-16 of step 1), the mass ratio of the nickel salt to the mesoporous molecular sieve carrier SBA-16 is (0.1-0.6):1, and impregnating the mesoporous molecular sieve carrier SBA-16 into the precursor solution by an impregnation method, and after ultrasonic dispersion, standing, vacuum drying, calcining, and grinding, the nickel-based catalyst with the mesoporous molecular sieve SBA-16 as a carrier is obtained;
[0010] Wherein, the nickel salt is at least one of chloride, acetate, oxalate, nitrate, sulfate or phosphate of the active component Ni;
[0011] The solvent is at least one of deionized water, methanol, ethanol, n-butanol, n-hexanol, acetic acid, ethyl acetate, n-pentane, n-hexane, and n-heptane;
[0012] The additive is at least one of citric acid, glucose, ethylene glycol, polysorbate and glycerol, and will be removed during the calcination process and will not exist in the components of the final catalyst.
[0013] In the step 1), the stirring temperature is 20-80° C., the stirring time is 6-48 hours, the drying temperature is 70-150° C., the drying time is 6-48 hours, and the calcination time is 3-8 hours.
[0014] In the step 2), the impregnation method is an equal volume impregnation method or an excess impregnation method, the impregnation temperature is room temperature, and the impregnation time is 4 to 24 hours; the ultrasonic dispersion time is 0.5 to 2 hours, the vacuum drying temperature is 40 to 100° C., and the drying time is 6 to 48 hours.
[0015] In the steps 1) and 2), the calcination atmosphere is air, the calcination heating rate is 1-5°C / min, and the calcination temperature is 400-700°C.
[0016] The catalyst uses the mesoporous molecular sieve SBA-16 material as a carrier and metal Ni as an active component; wherein the content of metal Ni is 10wt% to 30wt%, and the balance is the mesoporous molecular sieve SBA-16;
[0017] The specific surface area of the catalyst is 600-1000m 2 / g, pore volume is 0.3~0.9cm 3 / g, pore size is 1~10nm.
[0018] Preferably, the specific surface area of the catalyst is 788m 2 / g, pore volume is 0.71cm 3 / g, pore size is 7nm.
[0019] The active component Ni exists in the form of NiO and Ni2O3.
[0020] Preferably, in step 1), the stirring temperature is 30-70° C., and the stirring time is 12-24 h; the drying temperature is 80-120° C., and the drying time is 12-24 h; the calcination temperature is 450-600° C., and the calcination time is 4-7 h.
[0021] Preferably, in step 2), the immersion time is 6 to 12 hours; the ultrasonic dispersion time is 0.5 to 1 hour; the vacuum drying temperature is 60 to 80° C., and the drying time is 12 to 24 hours; the calcination temperature is 450 to 550° C., and the calcination time is 3 to 5 hours.
[0022] The present invention also provides an application of the nickel-based catalyst with the mesoporous molecular sieve SBA-16 material as a carrier in the CO2 methanation reaction, characterized in that the process conditions of the CO2 methanation reaction are: the reaction gas volume space velocity is 3500-35000 mL / g / h, the pressure is from normal pressure to 5.0 MPa, the temperature is 200-400°C, and the H2 / CO2 ratio in the reaction gas is 1-5.
[0023] The present invention discloses the following technical effects:
[0024] (1) The nickel-based catalyst with the mesoporous molecular sieve SBA-16 material as a carrier according to the present invention exhibits excellent activity and methane selectivity in the CO2 methanation reaction. The nickel-based catalyst is active in the temperature range of 200-400°C, and the optimal reaction temperature range is 300-350°C. When the catalyst reaches the optimal catalytic activity, the CO2 conversion rate is 100.0%, and the CH4 selectivity can reach at least 99%.
[0025] (2) The nickel-based catalyst with mesoporous molecular sieve SBA-16 as a carrier of the present invention uses mesoporous molecular sieve SBA-16 with large specific surface area, good heat transfer properties and stable chemical properties as a carrier. The interaction between the metal and the carrier in the prepared catalyst is strong, and the active components are highly dispersed on the surface of the carrier. Therefore, the catalyst has the advantages of high catalytic activity, good selectivity, and long life. The catalyst does not contain precious metal components, the preparation method is simple and convenient, and has potential industrial application value.
[0026] (3) The nickel-based catalyst with mesoporous molecular sieve SBA-16 as carrier described in the present invention is a three-dimensional cage-shaped SiO2 molecular sieve material. The three-dimensional structure makes the material mass transfer effect better. The molecular sieve contains a large number of mesopores and a small number of micropores. The larger cage-shaped pores can prevent the active components from thermal migration and sintering at high temperatures. It has shown broad application prospects in the fields of adsorption, biomedicine, environment and catalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the small angle XRD pattern of the mesoporous molecular sieve SBA-16;
[0028] Figure 2 TEM image of mesoporous molecular sieve SBA-16;
[0029] Figure 3 The activity diagram of CO2 hydrogenation to methane of the catalyst samples of Examples 1, 2, 4 and Comparative Examples 1-2;
[0030] Figure 4 The CO2 conversion rate of the catalyst prepared in Example 1 in a 100h life experiment;
[0031] Figure 5 The CH4 conversion rate of the catalyst prepared in Example 1 in the 100h life experiment; DETAILED DESCRIPTION
[0032] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0033] The "room temperature" of the present invention refers to 15 to 30°C, preferably 20 to 25°C.
[0034] The "normal pressure" in the present invention refers to 0.1 MPa.
[0035] If not otherwise specified, deionized water is generally used as the impregnation solvent in the present invention.
[0036] The detailed information of the reagents used in the examples of the present invention is shown in Table 1:
[0037] Table 1
[0038]
[0039]
[0040] Example 1
[0041] At 40°C, add 4g F127 to 200mL deionized water to dissolve, add 52.3g HCl solution, and then add 15g ethyl orthosilicate. After continuous stirring for 12h, the solution was crystallized at 90°C for 24h. Filter and wash with deionized water, and dry the obtained solid at 120°C for 12h, and finally calcine at 550°C for 5h, and naturally cool to room temperature to obtain molecular sieve SBA-16.
[0042] Dissolve 2.6232g of nickel nitrate hexahydrate in 2g of deionized water, and add 0.5g of citric acid monohydrate to prepare an aqueous solution of nickel nitrate. Then, 1.5g of the above-mentioned SBA-16 carrier is immersed in an aqueous solution of nickel nitrate in equal volume, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample is dried in a vacuum oven at 80°C for 12h. The dried solid product is placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature to obtain a nickel-based catalyst with a mass fraction of 30wt%.
[0043] Example 2
[0044] 1.3116g of nickel nitrate hexahydrate was dissolved in 2g of deionized water, and 0.25g of citric acid monohydrate was added to prepare an aqueous solution of nickel nitrate. Then, an equal volume of 1.5g of the SBA-16 carrier prepared in Example 1 was immersed in the aqueous solution of nickel nitrate, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample was dried in a vacuum oven at 80°C for 12h. The dried solid product was placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature to obtain a nickel-based catalyst with a mass fraction of 15wt%.
[0045] Example 3
[0046] Glucose was used to replace the citric acid monohydrate in Example 3, and the remaining steps were the same as those in Example 3 to prepare a nickel-based catalyst with a mass fraction of 15 wt%.
[0047] Example 4
[0048] 1.3116g of nickel nitrate hexahydrate was dissolved in 2g of deionized water to prepare an aqueous solution of nickel nitrate. Then, an equal volume of 1.5g of the SBA-16 carrier prepared in Example 1 was immersed in the aqueous solution of nickel nitrate, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample was dried in a vacuum oven at 80°C for 12h. The dried solid product was placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature to obtain a nickel-based catalyst with a mass fraction of 15wt%.
[0049] Comparative Example 1
[0050] 1.3116g of nickel nitrate hexahydrate was dissolved in 1.5g of deionized water to prepare an aqueous solution of nickel nitrate. Then, an equal volume of 1.8g of SBA-15 carrier was immersed in the aqueous solution of nickel nitrate, ultrasonically dispersed at room temperature for 1h, and allowed to stand for 6h. Subsequently, the impregnated sample was dried in a vacuum oven at 80°C for 12h. The dried solid product was placed in a muffle furnace, calcined at 550°C in an air atmosphere for 5h, and naturally cooled to room temperature. After grinding, a nickel-based catalyst with a mass fraction of 15wt% was obtained.
[0051] Comparative Example 2
[0052] The SBA-15 in Comparative Example 2 was replaced by a common SiO2 carrier, and the remaining steps were the same as those in Example 2 to prepare a nickel-based catalyst with a mass fraction of 15 wt%.
[0053] Comparative Example 3
[0054] The SBA-15 in the comparative example was replaced by an Al2O3 carrier, and the other steps were the same as those in Example 2 to prepare a nickel-based catalyst with a mass fraction of 15 wt%.
[0055] The test results of N2 physical adsorption and desorption experiments on all the carriers in Examples 1 to 4 and Comparative Examples 1 to 3 are listed in Table 2.
[0056] Table 2
[0057]
[0058] The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used in the CO2 methanation reaction, and the specific method was as follows:
[0059] Weigh 0.48g of the catalyst prepared in Examples 1 to 4 and Comparative Examples 1 to 3, and load it into a fixed bed reactor with a diameter of 6nm by the sandwich method. Before the reaction, purge the air with N2, and then reduce the catalyst at 500°C and pure H2 atmosphere for 2h. After the reduction, the N2 atmosphere drops to the reaction temperature and switches to the reaction gas to test the performance of the catalyst. The reaction gas composition is H2:CO2:N2=4:1:1, the reaction pressure is normal pressure, the reaction temperature is 300°C, and the reaction gas volume space velocity is 15,000mL / g / h. The reaction gas product is analyzed online using a gas chromatograph and a thermal conductivity detector (TCD).
[0060] The CO2 conversion rate and CH4 selectivity were calculated as follows, and the optimal catalytic activity results of the catalysts are listed in Table 3:
[0061] CO2 conversion rate: Conv%(CO2)=(1-CO2 amount in the product / CO2 amount in the raw gas)×100%;
[0062] CH4 selectivity: Sele%(CH4)=(amount of CO2 converted to CH4 / amount of CO2 converted)×100%;
[0063] Table 3
[0064]
[0065]
[0066] Combining the data of Examples 1 to 3 and Example 4, it can be found that the introduction of additives can improve the catalytic performance of the catalysis. This is because small molecule additives can reduce the size of the active component particles, the dispersion of the metal active component is improved, and the smaller Ni particle surface has more active sites, which is conducive to the adsorption and activation of the reaction gas, and the catalyst activity effect prepared by adding citric acid small molecules is the best. Comparing the catalyst activity data of Example 4 and Comparative Examples 1 to 3, it can be seen that among SBA-16, SBA-15, SiO2, and Al2O3 carriers, the catalyst effect prepared by the SBA-16 carrier catalyst is the best. This is because the SBA-16 carrier has a unique three-dimensional cage structure, each of which is connected to the surrounding eight cages through tiny channels. This three-dimensional interconnected pore structure is conducive to the transportation and flow of reactants and products, improves its mass transfer efficiency, and is conducive to improving the reaction activity. In addition, combined with the data of Example 1, it can be seen that the nickel content of the catalyst prepared by the present invention can reach 30wt%. From the data of Example 2, it can be seen that after adding appropriate additives, the application effect of the catalyst with a nickel content of 15wt% can still reach a carbon dioxide conversion rate of 100.0% and a methane selectivity of at least 99%. Therefore, under the optimal conditions, the carbon dioxide conversion rate of the nickel-based catalyst prepared in the present invention can reach 100.0%, and the methane selectivity can reach at least 99%.
[0067] The catalyst prepared in Example 1 was used in the CO2 methanation reaction and a 100-h life test was carried out under the optimal catalytic conditions. The performance was as shown in the data Figure 3 , Figure 4 shown.
[0068] Figure 3 , Figure 4 It shows that the catalyst prepared in Example 1 has a CO2 conversion rate of more than 92% and a selectivity of more than 99% after 100 hours of reaction under the optimal catalytic conditions, and has a long service life. This is because the unique cage structure and pore structure of SBA-16 have a confining effect, which can effectively inhibit the agglomeration of metal particles during the catalyst preparation and reaction process, thereby improving the stability of the catalyst. Under the optimal reaction conditions, the carbon dioxide conversion rate can reach 100.0%, the methane selectivity can reach at least 99%, and it has the advantages of good stability and great industrial prospects.
[0069] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A nickel-based catalyst with mesoporous molecular sieve SBA-16 as carrier, characterized in that: The catalyst is prepared by the following method, comprising the following steps: 1) Preparation of mesoporous molecular sieve carrier SBA-16: dissolving triblock surfactant F127 in deionized water, adding hydrochloric acid solution and then adding tetraethyl orthosilicate and stirring, the molar ratio of each component is F126: hydrochloric acid: deionized water: tetraethyl orthosilicate = (0.001-0.01): (2-12): (2.5-7.5): (70-300): 1; after crystallization, filtration, drying, calcination and grinding, a mesoporous molecular sieve carrier SBA-16 white powder is obtained; 2) dissolving the nickel salt in a solvent and adding an additive, preparing a precursor solution of a metal active component in a mass ratio of the additive to the nickel salt of (0-1.2):1, then adding the mesoporous molecular sieve carrier SBA-16 of step 1), the mass ratio of the nickel salt to the mesoporous molecular sieve carrier SBA-16 is (0.1-0.6):1, and impregnating the mesoporous molecular sieve carrier SBA-16 into the precursor solution by an impregnation method, and after ultrasonic dispersion, standing, vacuum drying, calcining, and grinding, the nickel-based catalyst with the mesoporous molecular sieve SBA-16 as a carrier is obtained; Wherein, the nickel salt is at least one of chloride, acetate, oxalate, nitrate, sulfate or phosphate of the active component Ni; The solvent is at least one of deionized water, methanol, ethanol, n-butanol, n-hexanol, acetic acid, ethyl acetate, n-pentane, n-hexane, and n-heptane; The additive is at least one of citric acid, glucose, ethylene glycol, polysorbate and glycerol, and will be removed during the calcination process and will not exist in the components of the final catalyst.
2. The nickel-based catalyst according to claim 1, characterized in that In the step 1), the stirring temperature is 20-80°C, the stirring time is 6-48h, the drying temperature is 70-150°C, the drying time is 6-48h, and the calcination time is 3-8h; In the step 2), the impregnation method is an equal volume impregnation method or an excess impregnation method, the impregnation temperature is room temperature, the impregnation time is 4 to 24 hours, the ultrasonic dispersion time is 0.5 to 2 hours, the vacuum drying temperature is 40 to 100° C., and the drying time is 6 to 48 hours; In the steps 1) and 2), the calcination atmosphere is air, the calcination heating rate is 1-5°C / min, and the calcination temperature is 400-700°C.
3. The nickel-based catalyst according to claim 1, characterized in that The catalyst uses the mesoporous molecular sieve SBA-16 material as a carrier and metal Ni as an active component; wherein the content of metal Ni is 10wt% to 30wt%, and the balance is the mesoporous molecular sieve SBA-16; The specific surface area of the catalyst is 600-1000m 2 / g, pore volume is 0.3~0.9cm 3 / g, pore size is 1~10nm.
4. The nickel-based catalyst according to claim 3, characterized in that The specific surface area of the catalyst is 788 m 2 / g, pore volume is 0.71cm 3 / g, pore size is 7nm.
5. The nickel-based catalyst according to claim 1, characterized in that In the step 1), the stirring temperature is 30-70°C, and the stirring time is 12-24h; the drying temperature is 80-120°C, and the drying time is 12-24h; the calcination temperature is 450-600°C, and the calcination time is 4-7h; In the step 2), the immersion time is 6 to 12 hours; the ultrasonic dispersion time is 0.5 to 1 hour; the vacuum drying temperature is 60 to 80° C., and the drying time is 12 to 24 hours; the calcination temperature is 450 to 550° C., and the calcination time is 3 to 5 hours.
6. Use of the nickel-based catalyst as claimed in claim 1 in a CO2 methanation reaction, characterized in that: The process conditions of the CO2 methanation reaction are: the reaction gas volume space velocity is 3500-35000 mL / g / h, the pressure is from normal pressure to 5.0 MPa, the temperature is 200-400°C, and the H2 / CO2 ratio in the reaction gas is 1-5.
Citation Information
Patent Citations
Core-shell type cerium oxide-coated nickel methanation catalyst and its preparation method and application
CN104971728B
Reverse Ni / CeO2 catalyst as well as preparation method and application thereof
CN116899568A
Cited By
Cerium skeleton substituted S-1 molecular sieve supported nickel metal catalyst, preparation method and application
CN120155234A
A cerium framework-substituted S-1 molecular sieve supported nickel metal catalyst, preparation method and application
CN120155234B